What Counts as Global Health? The Case of Clandestine Abortion Access Activist Networks - Macdonald, Margaret (Anthropologica, 2024)
Safe abortion access is an essential aspect of reproductive justice and key to reducing global rates of maternal mortality, yet within the global heath enterprise, the rhetoric of sexual and reproductive health and rights has not yet been realised in practice. Access to safe legal abortion remains inequitable globally and within nations and deaths due to unsafe abortion take their highest toll in the Global South in jurisdictions with restrictive laws. Clandestine abortion access activist networks have been filling this gap offering life, dignity and futures to the people who seek their services. What should we make of clandestine activist networks around the world that help people access medication abortion? Such groups have been important players in women’s reproductive health in many jurisdictions for decades – but have typically, by necessity and design, flown under the radar. If visibility, accountability and humanitarian appeal are essential characteristic of global health work, how do we acknowledge and understand the work of clandestine abortion access activist networks? Does it count as global health? In this essay I offer the notion of ‘critique in action’ to further our understanding of such networks and also consider the idea of abortion access activist networks as an anti-regime of global health.